#### Answer

{4}

#### Work Step by Step

$\frac{3x}{4}$ - 9 =-6
Step 1 : Multiply both the sides by 4
$\frac{3x}{4}$ . 4 - 9.4 =-6.4
Solve
3x - 36 = -24
Step 2 : Collect variable terms on one side and constants on the other side.
add 36 on both the sides
3x -36 + 36 = -24 + 36
3x = 12
Step 3: Divide both the sides by 3
$\frac{3x}{3}$ = $\frac{12}{3}$
x = 4
Now we check the proposed solution, 4 , by replacing x with 4 in the original equation.
Step 1: the original equation $\frac{3x}{4}$ - 9 =-6
Step2: Substitute 4 for x
$\frac{3. 4}{4}$ - 9 =-6
Step 3: Simplify
$\frac{12}{4}$ - 9 =-6
Step 4 : Divide $\frac{12}{4}$ = 3
3 -9 = -6
Solve
-6 =-6
Since the check results in true statement, we conclude that the solution set of the given equation is {4}.